THE IMPORTANCE OF LEARNING MORAL VALUES IN EARLY CHILDREN - Khulusinniyah Khulusinniyah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
As commanded by Allah SWT, of course parents or educators are obliged to educate children from childhood so that they become people of faith and fear of Allah SWT. The early childhood stage is a great initial opportunity to develop a child's personality, which will determine his future. This research is a field study that focuses on the results of data collection from certain informants. Field research can also be seen as a qualitative data collection method, meaning that it is intended to provide an in-depth study of how a social unit works. Results Instilling moral values ​​is very well applied from an early age. To find out the state of the moral values ​​of students in PAUD, researchers conducted interviews with teachers. According to the survey results, the answers were: "Instilling the moral values ​​of devotion to parents to children at this age, the teacher gives instructions, sets an example and gets children used to it every time they enter and leave the classroom. In class, they always shake hands (handshake) while kissing the hands of their elders. "old and hello." The conclusion of instilling moral values ​​in early childhood with the methods used by PAUD teachers is the tour method, the conversation method, the demonstration method, the storytelling method, the singing method and appointments. In general, the use of learning methods in PAUD has the advantages of each learning method that can develop aspects of child development, such as moral and religious values, social-emotional and specific learning experiences and provide hands-on experience for skilled children at home. Sebagaimana perintah Allah SWT, tentunya orang tua atau pendidik wajib mendidik anak sejak kecil agar menjadi orang yang beriman dan bertakwa kepada Allah SWT. Jenjang anak usia dini merupakan peluang awal yang besar untuk membina kepribadian anak, yang akan menentukan masa depannya. Penelitian ini merupakan penelitian lapangan (field study) yang menitikberatkan pada hasil pengumpulan data dari informan tertentu”. Penelitian lapangan juga dapat dilihat sebagai metode pengumpulan data kualitatif, artinya dimaksudkan untuk memberikan kajian mendalam tentang bagaimana sebuah unit sosial bekerja. Hasil. Penanaman nilai-nilai moral sangat baik diterapkan sejak dini. Untuk mengetahui keadaan nilai moral siswa di PAUD, peneliti melakukan wawancara dengan guru. Menurut hasil survei diperoleh jawaban: “Menanamkan nilai-nilai moral kepada anak sejak usia dini agar memiliki baktiyang tinggi kepada orang tua kepada sesama dan para guru. guru memberikan petunjuk, memberi contoh dan membiasakan anak setiap masuk dan meninggalkan ruang kelas. Di kelas, mereka selalu berjabat tangan (handshake) sambil mencium tangan yang lebih tua. "tua dan halo." Kesimpulan menanamkan nilai moral pada anak usia dini dengan metode yang digunakan oleh guru PAUD ialah metode tour, metode percakapan, metode demonstrasi, metode bercerita, metode menyanyi dan janji temu. Secara umum penggunaan metode pembelajaran di PAUD memiliki kelebihan dari masing-masing metode pembelajaran yang dapat mengembangkan aspek-aspek perkembangan anak, seperti nilai moral dan agama, sosial emosional dan pengalaman belajar yang spesifik dan memberikan pengalaman langsung bagi anak-anak terampil di rumah.